Intracranial Hemorrhage in Full Term Infants; A Follow-Up Study - Mehmet Şah İpek; Ayşegül Zenciroğlu; Mehpare Özkan; Hasibe Gökçe Çınar; Mustafa Aydın; Nurullah Okumuş (Güncel Pediatri)
Introduction: The aim of this study was to determine the risk factors related to, clinical presentation and outcome of intracranial hemorrhage among full-term newborn infants.Materials and Methods: Full-term newborn infants who were diagnosed with intracranial hemorrhage in the neonatal intensive care unit of Dr. Sami Ulus Maternity and Children’s Hospital, between 2005 and 2010, were reviewed retrospectively. Cases were diagnosed with ultrasonography, computed tomography, or magnetic resonance imaging. The infants followed an average of 36 months had been underwent neurologic evaluations. Results: Fourteen full-term infants with intracranial hemorrhage were identified. The half of cases presented within the first week of life (7/14), and the most common presenting sign was seizure (8/14). Bleeding were placed frequently intraventricular (9/14) and subarachnoid (7/14), while 8 patients had two or more hemorrhage areas. The majority of cases (11/14) had a causal or contributory risk factor for intracranial hemorrhage. Only one patient required neurosurgical intervention. Two patients died during the neonatal period, and another with severely handicapped at ten months of age. Of the survivors, two patients showed severe neurodevelopmental delay, while one patient showed mild. The remaining 8 patients had a favorable outcome. Conclusions: Intracranial hemorrhage in the term newborn is usually associated with perinatal risk factors. Because of neurodevelopmental outcome may surprisingly be normal, despite severe hemorrhage, the long-term outcome is difficult to predict. (Journal of Current Pediatrics 2012; 10: 85-91)